Differentiation of innovation behavior of manufacturing firms in the new member states: Cluster analysis on firm-level data - Anna Wziątek-Kubiak; Ewa Balcerowicz; Marek Pęczkowski (Center for Social and Economic Research (CASE), 2009)
This paper investigates the differences in innovation behaviour, i.e. differences in innovation sources and innovation effects, among manufacturing firms in three NMS: the Czech Republic, Hungary and Poland. It is based on a survey of firms operating in four manufacturing industries: food and beverages, automotive, pharmaceuticals and electronics. The paper takes into account: innovation inputs in enterprises, cooperation among firms in R&D activities, the benefits of cooperation with business partners and innovation effects (innovation outputs and international competitiveness of firms' products and technology) in the three countries. After employing cluster analysis, five types of innovation patterns were detected. The paper characterises and compares these innovation patterns, highlighting differences and similarities. The paper shows that external knowledge plays an important role in innovation activities in NMS firms. The ability to explore cooperation with business partners and the benefits of using external knowledge are determined by in-house innovation activities, notably R&D intensity.
Keywords: L25; O31; O32; O33; 330; Innovation patterns of firms; Strategy of innovation; Innovation behaviour; Innovation sources; Taxonomies of innovative firms; EU New Member States; Innovation; Innovationsdiffusion; Forschungskooperation; Internationaler Wettbewerb; Industrie; Clusteranalyse; Tschechien; Ungarn; Polen